1996
DOI: 10.1007/bf01411175
|View full text |Cite
|
Sign up to set email alerts
|

Stump pressure as a guide to the safety of permanent occlusion of the internal carotid artery

Abstract: Does the absolute value of the stump pressure (post-occlusion back pressure) become a useful index of a good collateral circulation? The authors continuously monitored the mean arterial pressure before, during and after 20-minute balloon test occlusion in 24 patients. The stump pressure was then compared with the results of 99mTc-hexa-methyl propyleneamine (99mTc-HMPAO) single photon emission computed tomography (SPECT) performed after 20 minutes of test occlusion. Patients who failed to tolerate even brief pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Proximal occlusion devices stop or reverse flow by occluding the carotid artery, much in the same way that a carotid endarterectomy accomplishes neuro-protection. An OP #40 mm Hg after occlusion of the CCA has been suggested to be a predictor of OI(12,13) during proximal protected CAS, and our study provides the definitive proof of this hypothesis.Measuring blood pressure (stump pressure) in the distal ICA during occlusion of the ICA is reported to be a reliable safety index to predict ischemia after permanent occlusion of the ICA (carotid sacrifice) performed for the management of complex cerebral aneurysms(14). Of note, the OP threshold of 40 mm Hg that we found associated with the development of OI corresponds to the literature regarding balloon test occlusion for carotid sacrifice used by cerebral angiographers(14).…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Proximal occlusion devices stop or reverse flow by occluding the carotid artery, much in the same way that a carotid endarterectomy accomplishes neuro-protection. An OP #40 mm Hg after occlusion of the CCA has been suggested to be a predictor of OI(12,13) during proximal protected CAS, and our study provides the definitive proof of this hypothesis.Measuring blood pressure (stump pressure) in the distal ICA during occlusion of the ICA is reported to be a reliable safety index to predict ischemia after permanent occlusion of the ICA (carotid sacrifice) performed for the management of complex cerebral aneurysms(14). Of note, the OP threshold of 40 mm Hg that we found associated with the development of OI corresponds to the literature regarding balloon test occlusion for carotid sacrifice used by cerebral angiographers(14).…”
supporting
confidence: 60%
“…An OP #40 mm Hg after occlusion of the CCA has been suggested to be a predictor of OI(12,13) during proximal protected CAS, and our study provides the definitive proof of this hypothesis.Measuring blood pressure (stump pressure) in the distal ICA during occlusion of the ICA is reported to be a reliable safety index to predict ischemia after permanent occlusion of the ICA (carotid sacrifice) performed for the management of complex cerebral aneurysms(14). Of note, the OP threshold of 40 mm Hg that we found associated with the development of OI corresponds to the literature regarding balloon test occlusion for carotid sacrifice used by cerebral angiographers(14). Even if other studies demonstrated in a different clinical setting that such low pressure is associated with the development of neurological symptoms, this is the first study to confirm this finding in the setting of proximal protected CAS.…”
mentioning
confidence: 99%
“…Also, the stump pressure at the occluded stump of the ICA is measured. [6][7][8] For the measurement of the cerebral blood flow, various devices including SPECT, 6,16) perfusion CT, [17][18][19] transcranial Dop pler, 20) and PETCT 21) are used. This conversely means that a universal device to measure the cerebral blood flow for the evaluation of ischemic tolerance has not been established.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] Whether or not the ICA was sufficiently occluded was confirmed according to the change in the stump pressure between before and after ICA occlusion.…”
Section: Procedures Of Btomentioning
confidence: 99%
“…Balloon test occlusion is generally performed in a preoperative setting when it is anticipated that one of the vessels supplying the brain will be sacrifi ced. Adjunctive maneuvers including hypotensive challenge [ 28 ], neuropsychological testing [ 29 ], somatosensory-evoked potentials [ 30 ], cerebral oximetry [ 31 ], and electroencephalography [ 32 ] may be considered to reduce the incidence of a false-negative result. In addition, the hemodynamic effects of occlusion can be assessed by measuring the stump pressure [ 69 ], angiographic control runs [ 33 ], transcranial Doppler [ 34 ], xenon 133 imaging [ 35 ], xenon CT [ 36 ], CT perfusion [ 37 ], PET [ 38 ], SPECT [ 39 ], and MR perfusion [ 40 ].…”
Section: Provocative Testing (See Chap 9 )mentioning
confidence: 99%